(untitled) (KYAMC Journal, 2017)
Introduction: Tuberculosis remains an infectious disease with a high prevalence worldwide and represents a major public health issue, especially in our subcontinent. Although venous thromboembolism is a rare complication of this disease, it may be a potentially life threatening event. Case presentation: We report a case of a 43 years male who was diagnosed as a case of pulmonary tuberculosis with tubercular pericardial effusion, developed deep venous thrombosis later in the course of the disease Conclusion: An association between inflammation induced by tuberculosis and a hypercoagulable state has been described. Therefore, the occurrence of deep venous thrombosis or pulmonary embolic episodes should be considered in patients with tuberculosis particularly during the first weeks of treatment. The physician’s awareness of these phenomena is important to an early diagnostic suspicion and prompt treatment in order to prevent fatal outcomes. KYAMC Journal Vol. 6, No.-1, Jul 2015, Page 598-600